Modeling Time-to-Collision for Road Work Zones under Varying Geometric and Traffic Conditions - Mr.S.B.Pawar; Mr.O.S.Bidkar; Dr.Y.P.Pawar; Dr.S.S. Kadam; Dr.S.D.Jagdale; Mr.S.R.Patil (The Bioscan, 2024)
Highway transportation is an essential mode of transportation from both accessibility and mobility perspectives. There is more traffic demand for road transportation than for other modes. In addition, there is haphazard development of road construction in all states of India. Road construction and maintenance activities are more common due to catering to more supplies of traffic demands. In particular, the work zone (WZ) is an area designed for road construction activities in which a specific road section is blocked. Therefore, traffic safety issues are much more for various road conditions. Therefore, studying traffic safety at the microscopic level for varying roadway, geometric, and traffic conditions is necessary. For this, the present study adopts a surrogate safety measure, namely time-to-collision (TTC), to study traffic safety at a microscopic level. The analysis involves the average value of TTC, deceleration rate to avoid a collision, and trajectories for geometric parameters of WZ. Modeling of TTC is performed for various geometric parameters of the WZ. The study outcome will benefit the construction authority in planning safety measures to minimize the probability of conflicts and correspondingly achieve safety reasonably.